2008
DOI: 10.1097/01.ccm.0000297954.45251.a9
|View full text |Cite
|
Sign up to set email alerts
|

Early enteral supplementation with key pharmaconutrients improves Sequential Organ Failure Assessment score in critically ill patients with sepsis: Outcome of a randomized, controlled, double-blind trial*

Abstract: In medical patients with sepsis, early enteral pharmaconutrition with glutamine dipeptides, vitamin C and E, beta-carotene, selenium, zinc, and butyrate in combination with an immunonutrition formula results in significantly faster recovery of organ function compared with control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(113 citation statements)
references
References 65 publications
2
85
0
10
Order By: Relevance
“…Four recent well-designed studies also failed to show a mortality benefit in the primary analyses, although none focused specifically on septic patients [631][632][633][634]. Two small studies on septic patients showed no benefit in mortality rates [635,636], but showed a significant reduction in infectious complications [636] and a faster recovery of organ dysfunction.…”
mentioning
confidence: 99%
“…Four recent well-designed studies also failed to show a mortality benefit in the primary analyses, although none focused specifically on septic patients [631][632][633][634]. Two small studies on septic patients showed no benefit in mortality rates [635,636], but showed a significant reduction in infectious complications [636] and a faster recovery of organ dysfunction.…”
mentioning
confidence: 99%
“…O conceito implica em indicar-se adequadamente cada imunonutriente, tais como glutamina, selênio, óleo de peixe (ácidos graxos -3) e arginina, a cada situação clínica, entre elas desnutrição, queimaduras, trauma, pacientes em estado crítico ou em síndrome de estresse respiratório agudo. Basearam sua argumentação no fato que os diversos estudos apresentados até o momento incorrem em erros metodológicos diversos, como seleção inadequada da amostra para estudo, uso de produtos para o estudo que associam diversos imunonutrientes 2,4,13,17,28,35,38,43 . Nesta linha de raciocínio, alguns autores estão buscando limitar o foco da amostra.…”
Section: Discussionunclassified
“…McQuiggan M. et al [80] отметил более быстрое восстановление функции желудочно кишечного тракта в группе больных (10 пациентов), получавших энтераль но глутамин в дозе 0,5 г/кг/сут в течение 10 и дней по сравне нию с контрольной группой (10 пациентов), поступивших в ста ционар в состоянии шока на фоне тяжелой травмы. Beale R. J. et al [81] сообщил, что у больных с тяжелым сепсисом, получав ших энтерально глутамин в дозе 30 г в первые сутки и 40 г в по следующие 9 дней, наблюдалось быстрое купирование призна ков органной диcфункции.…”
Section: влияние глутамина на функциональное состояние стенки кишечникаunclassified